IMPLEMENTATION OF THE BOS FUND PROGRAM AT SMPN 1 GEMPOL - Wibowo, Adelwina Hurry Putri; Sukmana, Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: this research aims to analyze the implementation of the School Operational Assistance Fund (BOS) program at SMPN 1 Gempol. Method: The method used in this study was direct interviews with a number of relevant informants to obtain accurate and in-depth data in accordance with the study objectives. Results: The results of Edward III's theoretical research show that Dana BOS. First, transparency in the use of BOS Funds at SMPN 1 Gempol has been well fulfilled through regular reporting, information accessibility and effective accountability. Second, information transparency, efficiency of priority allocation, and effectiveness in the quality of educational services are indicators of accountability for the use of BOS Funds at SMPN 1 Gempol. Third, the active involvement of various stakeholders—, starting from school principals, teachers, committees, parents, students, to the education department— is very crucial in ensuring transparency, accountability and accuracy of BOS Fund management targets at SMPN 1 Gempol. Fourth, the implementation of BOS Funds at SMPN 1 Gempol has succeeded in improving the quality of education through improving facilities, providing learning tools, extracurricular support and teacher training, which directly fosters student enthusiasm and discipline. The five BOS Funds have proven to be very crucial in improving facilities and infrastructure at SMPN 1 Gempol, supporting the quality of learning and comfort, despite challenges related to budget limitations and usage rules. Overall, the implementation of BOS Funds at SMPN 1 Gempol shows positive results in improving the quality of education, but needs continuous improvement so that the benefits can be felt optimally and evenly. Novelty: This study provides a comprehensive evaluation of the BOS Fund implementation at SMPN 1 Gempol by directly linking transparency, accountability, and stakeholder involvement with the improvement of educational quality, an approach that highlights both managerial and pedagogical impacts simultaneously.